2023
DOI: 10.1101/2023.04.12.536557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation and substrate specificity of the human P4-ATPase ATP8B1

Abstract: Asymmetric distribution of phospholipids in eukaryotic membranes is essential for maintaining cell integrity, signaling pathways, and vesicular trafficking. P4-ATPases, also known as flippases, participate in creating and maintaining this asymmetry through active transport of phospholipids from the exoplasmic to the cytosolic leaflet. In this study, we present a total of nine cryo-electron microscopy structures at a resolution ranging from 2.4 to 3.1 A, along with functional and computational studies of the hu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Based on these results, it is expected that asymmetrically localized PlaEtn by means of ATP8B2 is sensed, as in the case of PlsEtn, suggesting that ATP8B2 transports at least three phospholipids, including PlsEtn, PtdCho, and PlaEtn, where the ability of transport of the first two phospholipids was shown by either the TNBS modification method or NBD-PtdCho [ 31 , 34 ]. A study addressing the substrate specificity and structural analysis of ATP8B1, which has an 83% similarity to ATP8B2, revealed that several substrates, such as PtdCho, PtdSer, PtdIns, and plasmanylcholine, are transported by ATP8B1 [ 91 ]. Therefore, careful analyses involving structural analysis of ATP8B2 are indeed necessary to fully understand how three phospholipids are transported by ATP8B2.…”
Section: Future Perspectivementioning
confidence: 99%
“…Based on these results, it is expected that asymmetrically localized PlaEtn by means of ATP8B2 is sensed, as in the case of PlsEtn, suggesting that ATP8B2 transports at least three phospholipids, including PlsEtn, PtdCho, and PlaEtn, where the ability of transport of the first two phospholipids was shown by either the TNBS modification method or NBD-PtdCho [ 31 , 34 ]. A study addressing the substrate specificity and structural analysis of ATP8B1, which has an 83% similarity to ATP8B2, revealed that several substrates, such as PtdCho, PtdSer, PtdIns, and plasmanylcholine, are transported by ATP8B1 [ 91 ]. Therefore, careful analyses involving structural analysis of ATP8B2 are indeed necessary to fully understand how three phospholipids are transported by ATP8B2.…”
Section: Future Perspectivementioning
confidence: 99%